KAJIAN ETNOBOTANI DAN FISIKO KIMIA KULIT KAYU LABAN (Vitex pubescens Vahl) DI DESA LAPE KECAMATAN KAPUAS KABUPATEN SANGGAU KALIMANTAN BARAT - Adelina, Kesita; Wardenaar, Evi; Sisillia, Lolyta (JURNAL HUTAN LESTARI, 2014)
Bark laban in the Village Lape used by Dayak Pangkodan since the first generation to generation as a drink tea. This researches aims to determine the type laban that utilized by local people Dayak Pangkodan in the village Lape and to identify utilization bark laban. This research is also to determine the physic-chemical properties of young bark laban and old bark laban which are water content, extract content , viscosity, pH, saponins, flavonoids and tannins. The results of this research indicate that the type of species laban that used are Vitex pubescens Vahl. Ethnobotany study by the respondents who is the Dayak Pangkodan in the village Lape use bark laban as a drink tea generally at the time of farming activities, tea of bark laban more widely known use by parents, bark laban than as a nutritious drink tea for stomach ache. The results of physic-chemical indicate that the water content of the wet weight of old bark laban and young bark laban have differences, content old bark laban 21.18 % and 16.36 % for young bark laban. Level of young bark extract laban have a higher value than the old bark laban , old bark laban 0.48% and for young bark laban 0.58 % laban young . The viscosity of the old bark laban (2.04 Cps) and for young bark laban (2 Cps) showed no significant. The results of pH old bark laban 5.2 and young bark laban 5.4. Bark laban (Vitex pubescens Vahl ) have content of saponins, tannins and flavonoids. Keywords: Vitex pubescens Vahl, bark, ethnobotany, physico chemica